A structural equation modelling approach for Malaysian consumers' perspectives on e-commerce B2C transactions. (1st January 2012) - Thaw, Yi Yi; Dominic, P.D.D.; Mahmood, Ahmad Kamil
The continuous growth and development of successful e-commerce essentially relies upon consumers' trust in e-commerce transactions. In order to adopt e-commerce, a consumer needs to make judgments in an environment of critical conflicting forces, namely, security, privacy, trust, and risk concerns. This study focuses on the consumers' trust to adopt e-commerce, which comprises purchasing products and services from web vendors, thus employing the model of business to consumer (B2C) e-commerce. The results of the study show that consumers' perceived risk influences their trust in e-commerce transactions, while the concept of perceived privacy evidences itself mainly through perceived security as well as trustworthiness of web vendors. In addition, the institutional trust influences a consumers' perceived risk in e-commerce transactions. The findings also suggest that economic incentives and institutional trust have relationships with consumers' perceived privacy. The overall model fit is tested by structural equation modelling (SEM) using AMOS 18.0 and the hypothesis, assumptions for SEM and descriptive statistics are analysed using SPSS 12.0.